Pengaruh Kombinasi Pakan terhadap Kemampuan Larva Tenebrio molitor dalam Mendegradasi Limbah Masker Medis Surgical - Novia Gesriantuti; Yeeri Badrun; Elm Yolanda (Sistem Informasi, 2022)
The disposable use of medical masks causes a buildup of medical waste masks that can pollute the environment. One of alternative method used to decant a medical mask is the use of the insect Tenebrio molitor. However, the larvae ability to reduce the rate of the masks is not optimal, so it is necessary to combine the diet with organic waste. The purpose of this study is to identify the potential of the larvae T. molitor and so it need to know the weight of the larvae bodies by giving advanced surgical medical masks combined with the organic waste of pineapple peel, papaya peel, dregs of tofu, and palm meal. The method used is a Completely Random Design (CRD) with 4 treatment and 3 repetition. Research indicates that the larvae T. molitor were able to descale the surgical masks of organic waste. The rate of biodegradation of surgical medical masks is estimated at 1,75 gr/days, surgical medical mask + papaya peel 1,73 gr/days, surgical medical mask + pineapple peel 1,72 gr/days and surgical medical mask + palm covers 1,25 gr/days. Correlation analysis obtained r = 0,7413 meaning indicates a strong correlation between died of the combination of surgical medical masks and organic waste on increase the larvae body weight. Keywords: Biodegradation, Organic Waste, Surgical Medical Mask, Tenebrio molitor Larvae